Formation of Value-Normative Complex in the Culture of Small Entrepreneurship: Comparative Analysis of Two Markets in Magadan Region - Ефим Сергеевич Фидря (Journal of Economic Sociology, 2010)
The paper is devoted to the value-normative complex in the culture of small entrepreneurship. The analysis is based on the empirical research of two local markets: computers and office equipment and the market of car spare parts.